Advances in group processes - Kalkhoff, Will; Thye, Shane R.; Lawler, Edward J. (Advances in group processes ;, 2023)
Advances in Group Processes publishes theoretical analyses, reviews, and theory based empirical chapters on group phenomena. The series adopts a broad conception of 'group processes'. This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, trust, justice, social influence, identity, decision-making, intergroup relations, and social networks. Previous contributors have included scholars from diverse fields including sociology, psychology, political science, economics, business, philosophy, computer science, mathematics, and organizational behavior. Volume 40 brings together papers that address theoretical and empirical issues in small groups and organizational research related to: The role of affect in shaping perceptions of the police and the predisposition to mass violence The shaping of prosocial behaviors (e.g., pro-environmental behaviors) by various social/societal factors, such as the shape and density of one's personal networks Differences in social status, its role in producing and sustaining social inequality and the unintended consequences of initiatives such as interventions designed to lessen status-based inequalities and level the playing field within the workplace. Reflecting a range of novel approaches from leading scholars in the field, this volume explores the relevance of group processes in analysing social status, iniquities and behaviors.